(untitled) (Modern education and development, 2025)
Communication extends beyond words to implied meanings, or implicature, which varies across cultures. While some cultures favor direct speech, others rely on indirect expressions, leading to potential misunderstandings in intercultural interactions. This paper examines cultural differences in implicature and emphasizes the importance of pragmatic awareness for effective global communication.